1961
DOI: 10.1002/pen.760010307
|View full text |Cite
|
Sign up to set email alerts
|

The effect of extrusion variables on the fundamental properties of tubular polythene film

Abstract: The mechanism of formation of tubular polythene film is a complicated process, and extensive studies have shown that the properties of the film made are influenced profoundly and in a complex way both by the processing conditions used by certain design features of the equipment. Studies of the effect of the extrusion variables on the more important film properties, both optical and mechanical, are reviewed in this paper. The results are discussed in terms of the fundamental nature of polythene film, its surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1971
1971
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 4 publications
0
17
0
Order By: Relevance
“…There is general agreement among the workers who have investigated sharkskin that, for a particular polymer, shark skin occurs at a fixed linear velocity rather than at a cri tical shear rate (6,7,9). This is well illustrated by Clegg (7) who showed that the onset of sharkskin is independent of die diameter but considerably delayed by increasing temperature.…”
Section: Influence Of Extrusion Variablesmentioning
confidence: 71%
“…There is general agreement among the workers who have investigated sharkskin that, for a particular polymer, shark skin occurs at a fixed linear velocity rather than at a cri tical shear rate (6,7,9). This is well illustrated by Clegg (7) who showed that the onset of sharkskin is independent of die diameter but considerably delayed by increasing temperature.…”
Section: Influence Of Extrusion Variablesmentioning
confidence: 71%
“…In addition, a lot of investigations have shown that the majority of light scattering is resulted from the surface roughness, and in this case, the dominating cause for such roughness is crystallization on and beneath the surface. [27][28][29][30][31] Therefore, we assume that the transmittance loss of PVDF and HFP11 thin films can be attributed to light scattering from surface textures derived from crystalline domain and its grain boundaries. Figure 5 illustrates surface morphology of the PVDF and P(VDF-co-HFP) copolymer films.…”
Section: Effect Of Crystallinity On Surface Morphology and Optical Trmentioning
confidence: 99%
“…It was first given extensive attention in the 1950s and early 1 9 6 0~~~"~ The first serious discussions related to tubular film characterization are those of Huck and Clegg. 48 A quantitative method of experimental investigation was devised by Clampitt et al49 This involves the measurement of the transmissivity T defined by 34 VOL. 8, NO.…”
Section: Haze In Filmsmentioning
confidence: 99%